Riverine Ecosystem Management: Science for Governing Towards a Sustainable Future - Schmutz, Stefan; Sendzimir, Jan (Aquatic Ecology Series, 2018)
Aquatic Ecology; Ecosystem Services; Environmental Management; Freshwater Science; River Restoration; Sustainable River Management; Water Pollution